PENGARUH RETURN ON EQUITY DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGES - Chau, Sheva Ordelia; Evadne, Angie (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Abstract This research aims to test and analyze the influence of return on equity (ROE) and current ratio (CR) on company value in food and beverage companies listed on the IDX in the 2019-2022 period. The sampling method in this research uses a purposive sampling technique, using quantitative data types involving 108 data from 27 food and beverages companies listed on the Indonesia Stock Exchange. The data source in this research is secondary data obtained from financial reports, using a ratio scale. The analytical method used is multiple linear regression analysis. The results of this research show that Return On Equity (ROE) has a significant positive effect on company value. Meanwhile, the Current Ratio (CR) has a positive and insignificant effect on company value.